Biosorption study of magnesium, zinc, iron and selene in Spirulina platensis high concentration crops (Research, Society and Development, 2021)
Mineral biosorption is a technique that can bring significant gains to the production of functional biomass. The results guarantee economy (due to the absence of mineral addition in dry biomass), minimization of time and a step by step elimination in the production process. The aim of the present work was to study the incorporation of zinc, magnesium, iron and selenium in the biomass of Spirulina platensis through the application of central composite factorial designs. The experiments were performed in a vegetative greenhouse in 10-liter photobioreactors, aiming the maximum absorption of the minerals over five days. Significant influence was observed in the incorporation of magnesium (410 mg.100-1g) and zinc (34.84 mg.100-1g). It was also observed in the incorporation of Fe (73.5 mg.100-1g) and selenium (1,738.81 mg.100-1g), showing the potential use of the technique to incorporate these minerals in Spirulina platensis biomass and ensuring wide application of this raw in foods and supplements.